PENGARUH DANA BOS DAN SARANA PRASARANA SEKOLAH TERHADAP HASIL BELAJAR SISWA KELAS XI SMK NEGERI 1 SURAKARTA TAHUN AJARAN 2015/2016 - Inda Fresti Puspitasari; Bambang Wasito Adi; Salman Alfarisy Totalia (BISE: Jurnal Pendidikan Bisnis dan Ekonomi, 2018)
The purposes of this study are to testt: (1) BOS funds influence to the learning outcomes of class XI student of SMK Negeri 1 Surakarta academic year 2015/2016, (2) the effect of school infrastructure on learning outcomes of class XI student of SMK Negeri 1 Surakarta academic year 2015/2016, (3) Effect of BOS funds and school infrastructure simultaneously to the learning outcomes of class XI student of SMK Negeri 1 Surakarta.Population in this study were all students of class XI in SMK Negeri 1 Surakarta academic year 2015/2016 and all the teachers that administer subjects in the eleventh grade. Sampling technique that used was proportional random sampling to determine the sample of students, and saturated sampling techniques to determine the sample of teachers. This research used descriptive quantitative approach. To obtain the data about BOS funds and school infrastructure Data was collected by using questionnaire technique (to obtain primary data) and structured interview techniques to obtain secondary data. Technique analysis dat a that used in this research is multiple linear regression analysis.The results of this study are follows: (1) there is positive and significant correlation between the BOS and school infrastructure simultaneously on student learning outcomes. (2) there is a positive and significant influence between BOS and student learning outcomes, by t- test results are known that Ho rejected and Ha accepted. (3) there are significant positive and significant correlation between school infrastructure and student learning outcomes, Based on t-test  results  can  be  concluded  that  if  school  infrastructures  are good,  student  learning outcomes can be increased too.